Dead coverage as soil conservationist practice - Cândido, H.; Silva, D. (Scientific Electronic Archives, 2019)
Soil degradation and erosion loss due to inadequate management pose a serious threat to agricultural productivity and contribute to the aggravation of environmental impacts. Soil, vegetative and mechanical practices of soil conservation are being developed to assist in the attenuation of these problems. The present research was carried out with the objective of evaluating the effect of mulching in the conversation of a sandy loam soil in the state of Mato Grosso. The study was developed under field conditions at the Federal University of Mato Grosso, Rondonópolis Campus and a completely randomized design with two treatments, with and without vegetation cover, where soil temperature, spontaneous plant quantification, soil moisture and relative humidity of the soil surface. It was verified that mulching kept the soil with a temperature gradient around two degrees lower than the uncovered treatment, besides reducing the emergence of spontaneous plants in 36 times and raising soil moisture by approximately four degrees, but not had an effect on soil surface moisture. Therefore, the use of mulch is an advantageous practice, which improves the hydrothermal characteristics of the soil and reduces the incidence of spontaneous plants